Cameroon : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This paper presents key discussions of Cameroon's 2013 Article IV Consultation. Economic activity in Cameroon has continued to recover gradually from the global financial crisis in 2008-2009, and inflation has remained subdued. In light of growing vulnerabilities, the report suggests to adopt a plan to reduce fuel subsidies gradually, accompanied by targeted social programs for the neediest, to free up resources for public investment. It is also necessary to accelerate resolution of distressed banks and enhance the regulatory framework to promote lending.